Penguatan Profil Pelajar Pancasila Melalui Tradisi Gropyokan Iwak Sebagai Sumber Belajar IPS - Prasetyo Utomo, Eko (Antroposen: Journal of Social Studies and Humaniora, 2023)
The aims to find out the procession of the Gropyokan Iwak tradition and the dimensions of Pancasila student profiles in the Gropyokan Iwak tradition as social studies learning resources. The problem is focused on the Gropyokan Iwak Guna tradition as a social studies learning resource in schools to strengthen the Profil Pelajar Pancasila. The data were collected through in-depth interviews and documentation and were analyzed qualitatively. This study concludes that the Gropyokan Iwak procession is carried out during the dry season which begins with a joint prayer while asking permission led by a religious leader. The peak of the procession is carried out with the community entering the reservoir together and catching fish. This tradition is interpreted by the people around the Sonorejo reservoir as local wisdom that can encourage the process of social integration in society through a process of direct social interaction. The sub-element dimensions of the Pancasila student profile appear, namely 1) understanding of beliefs; 2) understand the connectedness of the earth's ecosystems; 3) protect the natural environment; 4) explore and compare cultural knowledge, beliefs, and practices; 5) participate in the joint decision-making process; 6) cooperation; 7) communication to achieve common goals; 8) positive interdependence; 9) social coordination; 10) Confident, resilient, and adaptive; 11) Identify, clarify, and process information and ideas; and 12) produce original ideas, works and actions. The character dimensions of Pancasila student profiles in the Gropyokan Iwak tradition can be integrated into social studies learning materials integrated thematically of the social life of the community.